Relationship Between BMI, Hemoglobin Levels, and Dur ation of Hemodialysis with Blood Pressure Changes Pressure at Praya Hospital - Juna, Pande Agus Arta; Utama , Lalu Buly Fatrahady; Lestari, Novianti Anggie; Sherliyanah, Sherliyanah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Hemodialysis (HD) is a kidney replacement therapy by filtrating blood outside the body using a dialysis machine. Intradialysis complications such as hypotension and intradialysis hypertension are one of the abnormal conditions that occur during the hemodialysis process. The purpose of this study in RSUD Praya was to evaluate the relationship between IMT, hemoglobin level, and duration of hemodialysis with changes in blood pressure during the hemodialysis process. This study used a cross-sectional approach and was observational quantitative analytic in nature. Sampling was done using the total sampling method. The sample size of this study was 45 samples. Data were tested using spearmen rank. The findings of 45 respondents, most of them have stable blood pressure 24 people (53.3%), while 10 people (22.2%) have decreased blood pressure, and 11 people (24.4%) have increased blood pressure. There was a significant correlation between body mass index and blood pressure changes (p=0.028). Hemoglobin levels were not associated with blood pressure changes (p=0.574). There was a strong relationship between hemodialysis duration and blood pressure changes (p=0.009). There is a relationship between BMI, duration of hemodialysis and blood pressure changes during hemodialysis process and there is no relationship between hemoglobin levels and blood pressure changes during hemodialysis process. The conclusion is that body mass index and duration of hemodialysis affect blood pressure changes in hemodialysis patients at Praya Regional Hospital, while hemoglobin levels have no influence on blood pressure changes in hemodialysis patients at Praya Regional Hospital.